Bridging the human resource gap in surgical and anesthesia care in low-resource countries: a review of the task sharing literature - Tigistu Ashengo; Alena Skeels; Elizabeth J. H. Hurwitz; Eric Thuo; Harshad Sanghvi (BMC, 2017)
Abstract Task sharing, the involvement of non-specialists (non-physician clinicians or non-specialist physicians) in performing tasks originally reserved for surgeons and anesthesiologists, can be a potent strategy in bridging the vast human resource gap in surgery and anesthesia and bringing needed surgical care to the district level especially in low-resource countries. Although a common practice, the idea of assigning advanced tasks to less-specialized workers remains a subject of controversy. In order to optimize its benefits, it is helpful to understand the current task sharing landscape, its challenges, and its promise. We performed a literature review of PubMed, EMBASE, and gray literature sources for articles published between January 1, 1996, and August 1, 2016, written in English, with a focus on task sharing in surgery or anesthesia in low-resource countries. Gray literature sources are defined as articles produced outside of a peer-reviewed journal. We sought data on the nature and forms of task sharing (non-specialist cadres involved, surgical/anesthesia procedures shared, approaches to training and supervision, and regulatory and other efforts to create a supportive environment), impact of task sharing on delivery of surgical services (effect on access, acceptability, cost, safety, and quality), and challenges to successful implementation. We identified 40 published articles describing task sharing in surgery and anesthesia in 39 low-resource countries in Africa and Asia. All countries had a cadre of non-specialists providing anesthesia services, while 13 had cadres providing surgical services. Six countries had non-specialists performing major procedures, including Cesarean sections and open abdominal surgeries. While most cadres were recognized by their governments as service providers, very few had scopes of practice that included task sharing of surgery or anesthesia. Key challenges to effective task sharing include specialists' concern about safety, weak training strategies, poor or unclear career pathways, regulatory constraints, and service underutilization. Concrete recommendations are offered.